SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN LANGSUNG TUNAI DANA DESA BERBASIS WEBSITE - Nur Aizah; Octa Sofyan Firmandala, Legi; Azise, Nur (UNIVERSITAS STEKOM, 2025)
The Village Fund Cash Assistance Program (BLT-DD) is a government effort to provide support to rural communities affected by the economic crisis, especially due to the COVID-19 pandemic. In Sidomukti Village, the implementation of BLT-DD has been running well, but there are still obstacles in terms of efficiency, accuracy, and transparency in the beneficiary selection process. This research aims to design and build a website-based Decision Support System (SPK) using the Simple Additive Weighting (SAW) method that can improve the effectiveness and accuracy of determining prospective BLT-DD recipients. Data collection methods include interviews and document studies, and use a quantitative descriptive approach to analyze data. The results showed that the implementation of a web-based system can speed up the selection process, reduce the potential for errors, and increase the transparency of information to the community, so that it can help village officials in managing social assistance more effectively, ensuring that assistance is right on target, and increasing community satisfaction with the BLT-DD program.